Tyrosine Kinase Inhibitor Pazopanib Inhibits Platelet Procoagulant Activity in Renal Cell Carcinoma Patients - Tullemans, Bibian M. E.; Nagy, Magdolna; Sabrkhany, Siamack; Griffioen, Arjan W.; oude Egbrink, Mirjam G. A.; Aarts, Maureen; Heemskerk, Johan W. M.; Kuijpers, Marijke J. E. (Frontiers in Cardiovascular Medicine, 2018)
Pazopanib is an angiostatic tyrosine kinase inhibitor (TKI) presently used for cancer treatment, particularly in patients with renal cell carcinoma (RCC). This treatment can be accompanied by mild bleeding as an adverse effect. Given the role of protein tyrosine kinases in platelet activation processes, we investigated whether and how pazopanib can affect platelet functions in purified systems and during treatment of advanced RCC patients. In isolated platelets from healthy volunteers, pazopanib dose-dependently reduced collagen-induced integrin activation and secretion, as well as platelet aggregation. Pazopanib addition diminished glycoprotein (GP) VI-dependent tyrosine phosphorylation of multiple platelet proteins, including the tyrosine kinase Syk. Furthermore, pazopanib inhibited GPVI-induced Ca2+ elevation, resulting in reduced exposure of the procoagulant phospholipid phosphatidylserine (PS). Upon perfusion of control blood over a collagen surface, pazopanib inhibited thrombus size as well as PS exposure. Blood samples from ten RCC patients were also analyzed before and after 14 days of pazopanib treatment as monotherapy. This treatment caused an overall lowering in platelet count, with three out of ten patients experiencing mild bleeding. Platelets isolated from pazopanib-treated patients showed a significant lowering of PS exposure upon activation. In addition, platelet procoagulant activity was inhibited in thrombi formed under flow conditions. Control experiments indicated that higher pazopanib concentrations were required to inhibit GPVI-mediated PS exposure in the presence of plasma. Together, these results indicated that pazopanib suppresses GPVI-induced platelet activation responses in a way partly antagonized by the presence of plasma. In treated cancer patients, pazopanib effects were confined to a reduction in GPVI-dependent PS exposure. Together with the reduced platelet count, this may explain the mild bleeding tendency observed in pazopanib-treated patients.